Analysis of the Prophet's Interaction Patterns from the Perspective of Islamic Communication in the Tafsir Al-Mishbah and Al-Munir - Muhammad Fairuz Asra Hafit; Muhammad Syahrial Razali Ibrahim (UIN Fatmawati Sukarno Bengkulu, 2026)
Prophetic communication in the Qur’an serves as the ideal model for Islamic da‘wah, yet comprehensive insight into the interaction patterns of Noah, Abraham, Moses, Jesus, and Muhammad (peace be upon them) remains limited. This study examines these patterns through Tafsir al-Mishbah by M. Quraish Shihab and Tafsir al-Munir by Wahbah al-Zuhaylī. A descriptive-analytical library study with a comparative approach; primary data were drawn from the two tafsirs and secondary data from related literature. Thematic analysis extracted verbal, non-verbal, and contextual communication features from relevant Qur’anic verses. All prophets display uniform noble traits—patience, wisdom, empathy, and audience adaptation. Noah exemplifies persistent preaching; Abraham employs rational and symbolic argument; Moses uses gentle speech against Pharaoh; Jesus combines miracles with wise discourse; Muhammad applies consultation and gentle words. Their roles encompass bearer of glad tidings (basyir), warner (nadzīr), explainer (mubayyin), and illuminating lamp (sirāj munīr). The prophetic model is ethically grounded and context-sensitive, offering a viable framework for contemporary da‘wah. The findings recommend integrating these insights into Islamic education and digital preaching to cultivate effective, ethical Muslim communicators.